A Low‐Power CuSCN Hydrogen Sensor Operating Reversibly at Room Temperature. (6th November 2021) - Kabitakis, Viktoras; Gagaoudakis, Emmanouil; Moschogiannaki, Marilena; Kiriakidis, George; Seitkhan, Akmaral; Firdaus, Yuliar; Faber, Hendrik; Yengel, Emre; Loganathan, Kalaivanan; Deligeorgis, George; Tsetseris, Leonidas; Anthopoulos, Thomas D.; et al.
Abstract: Hydrogen is attractive as an abundant source for clean and renewable energy. However, due to its highly flammable nature in a range of concentrations, the need for reliable and sensitive sensor/monitoring technologies has become acute. Here a solid‐state hydrogen sensor based on solution‐processable p‐type semiconductor copper thiocyanate (CuSCN) is developed and studied. Sensors incorporating interdigitated electrodes made of noble metals (gold, platinum, palladium) show excellent response to hydrogen concentration down to 200 ppm while simultaneously being able to operate reversibly at room temperature and at low power. Sensors incorporating Pd electrodes show the highest signal response of 179% with a response time of ≈400 s upon exposure to 1000 ppm of hydrogen gas. The experimental findings are corroborated by density functional theory calculations, which highlight the role of atomic hydrogen species created upon interaction with the noble metal electrode as the origin for the increased p‐type conductivity of CuSCN during exposure. The work highlights CuSCN as a promising sensing element for low‐power, all‐solid‐state printed hydrogen sensors. Abstract : Low‐power hydrogen sensors based on the wide‐bandgap p‐type semiconductor CuSCN show excellent response to low concentrations of hydrogen at room temperature. The increase in conductivity of CuSCN upon exposure is attributed to the interaction between molecular hydrogen and the noble metal electrode which act as catalysts for hydrogen chemisorption within CuSCN.